2019
DOI: 10.3389/fphar.2019.00657
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics of Meglumine Antimoniate in Patients With Cutaneous Leishmaniasis

Abstract: Control of cutaneous leishmaniasis (CL) in the Americas is dependent on chemotherapy with parenteral pentavalent antimonials. High rates of treatment failure urge the search for predictive and prognostic markers of therapeutic responsiveness. In this study, we aimed to identify biomarkers of therapeutic response during treatment with meglumine antimoniate (MA). We conducted untargeted metabolomic profiling of plasma samples from CL patients (n = 39; 25 who cured and 14 who did not cure), obtained before and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Our results argue that in patients who failed the conventional treatment, there is a potential persistent Finally, the integrative analysis of protein with lipidomic profiles revealed that the lipid mediators are a major component able to discriminate treatment outcomes. A recently published study used the similar metabolomic approach to identify predictive biomarkers of the treatment outcome in patients with CL caused by L. viannia (Vargas et al, 2019). As noted in present study, drug exposure was able to modulate the metabolic products, and this change was associated with immune response and outcome of treatment (Vargas et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our results argue that in patients who failed the conventional treatment, there is a potential persistent Finally, the integrative analysis of protein with lipidomic profiles revealed that the lipid mediators are a major component able to discriminate treatment outcomes. A recently published study used the similar metabolomic approach to identify predictive biomarkers of the treatment outcome in patients with CL caused by L. viannia (Vargas et al, 2019). As noted in present study, drug exposure was able to modulate the metabolic products, and this change was associated with immune response and outcome of treatment (Vargas et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…A recently published study used the similar metabolomic approach to identify predictive biomarkers of the treatment outcome in patients with CL caused by L. viannia (Vargas et al, 2019). As noted in present study, drug exposure was able to modulate the metabolic products, and this change was associated with immune response and outcome of treatment (Vargas et al, 2019). Here, we demonstrated that among the lipids, the 12-oxo-HETE, 5-oxo-HETE, and LTB 4 stood out as the most robust biomarkers in the predictive model employed.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the infection-induced host metabolic alterations could lead to new treatments for parasitic diseases [29], particularly host-targeted drug therapy focused on pathways otherwise redundant to the host but important for parasite invasion, replication and survival [30], or on mitigating damage caused by the parasite [29]. In addition, host metabolism, as measured in plasma samples, has been shown to be able to serve as an indicator of response to CL treatment [31]. Several studies have investigated Leishmania metabolism during in vitro macrophage infection ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the infection-induced host metabolic alterations could lead to the identification of potential targets and subsequently to drug development for parasitic diseases [ 17 ], particularly host-targeted drug therapy focused on pathways otherwise redundant to the host but important for parasite invasion, replication and survival [ 18 ], or on mitigating damage caused by the parasite [ 17 ]. In addition, changes in the host plasma metabolite abundance, including pyruvate, taurine and N -acetylglutamine, can serve as an indicator of response to CL treatment [ 19 ]. Several studies previously investigated Leishmania and host metabolism during in vitro macrophage infection [ 20 , 21 , 22 , 23 ], or in amastigotes purified from mouse granulomatous lesions [ 24 ], but there is still a lack of knowledge of host metabolic responses during in vivo infection.…”
Section: Discussionmentioning
confidence: 99%